Sub-regional anterior cingulate cortex functional connectivity revealed default network subsystem dysfunction in patients with major depressive disorder. Issue 10 (10th July 2021) - Peng, Xiaolong; Wu, Xiaoping; Gong, Ruxue; Yang, Rui; Wang, Xiang; Zhu, Wenzhen; Lin, Pan
Abstract: Background: Major depressive disorder (MDD) is a prevalent mental disorder characterized by impairments in affect, behaviour and cognition. Previous studies have indicated that the anterior cingulate cortex (ACC) may play an essential role in the pathophysiology of depression. In this study, we systematically identified changes in functional connectivity (FC) for ACC subdivisions that manifest in MDD and further investigated the relationship between these changes and the clinical symptoms of depression. Methods: Sub-regional ACC FC was estimated in 41 first-episode medication-naïve MDD patients compared to 43 healthy controls. The relationships between depressive symptom severity and aberrant FC of ACC subdivisions were investigated. In addition, we conducted a meta-analysis to generate the distributions of MDD-related abnormal regions from previously reported results and compared them to FC deficits revealed in this study. Results: In MDD patients, the subgenual and perigenual ACC demonstrated decreased FC with the posterior regions of the default network (DN), including the posterior inferior parietal lobule and posterior cingulate cortex. FC of these regions was negatively associated with the Automatic Thoughts Questionnaire scores and largely overlapped with previously reported abnormal regions. In addition, reduced FC between the caudal ACC and precuneus was negatively correlated with the Hamilton Anxiety Scale scores. We also found increased FC between the rostral ACC and dorsal medial prefrontal cortex. Conclusions: Our findings confirmed that functional interaction changes in different ACC sub-regions are specific and associated with distinct symptoms of depression. Our findings provide new insights into the role of ACC sub-regions and DN in the pathophysiology of MDD.